2016
DOI: 10.1177/1461444814567987
|View full text |Cite
|
Sign up to set email alerts
|

Revaluating urban space through tweets: An analysis of Twitter-based mobile food vendors and online communication

Abstract: The rise of mobile food vending in US cities combines urban space and mobility with continuous online communication. Unlike traditional urban spaces that are predictable and known, contemporary vendors use information technology to generate impromptu social settings in unconventional and often underutilized spaces. This unique condition requires new methods that interpret online communication as a critical component in the production of new forms of public life. We suggest qualitative approaches combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…[50][51][52] The process of digitalization has also contributed to the emergence of physical spaces such as internet cafés 53 and, more recently, innovations such as just-in-time restaurants, in the form of food trucks or other mobile food services that take food vending to different locations based on an online dialogue with consumers to identify where the demand is at that moment in time. 54 Regarding food product properties, this review found examples of emerging food products such as 3D printed food. This includes a variety of products, from 3D printed pastries, to 3D printed meat and other products using a blend based on fruits and vegetables.…”
Section: External Domainmentioning
confidence: 99%
“…[50][51][52] The process of digitalization has also contributed to the emergence of physical spaces such as internet cafés 53 and, more recently, innovations such as just-in-time restaurants, in the form of food trucks or other mobile food services that take food vending to different locations based on an online dialogue with consumers to identify where the demand is at that moment in time. 54 Regarding food product properties, this review found examples of emerging food products such as 3D printed food. This includes a variety of products, from 3D printed pastries, to 3D printed meat and other products using a blend based on fruits and vegetables.…”
Section: External Domainmentioning
confidence: 99%
“…Other names for food trucks include mobile food vendors; catering trucks; gourmet food trucks; and mobile restaurants. Due to their mobility, food truck vendors are able to offer a wider variety of menu items and attract new customers who prefer outdoor dining (Martin, 2014; Wessel et al ., 2015). Considered a trendy activity, visiting food trucks has become a cultural phenomenon in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…The nutrition of the population personalization, due to individual food characteristics, puts forward new requirements for digital technologies that ensure the production of food. The formation of an innovative type of reproduction required approaches to create a new organizational and economic mechanism for its regulation based on new intellectual products [5][6].…”
Section: Introductionmentioning
confidence: 99%